The impact of corporate social responsibility on strategic risk: The moderating effect of ethical decision-making / Zhang Ye ... [et al.] - Zhang, Ye; Kuan, Siaw Vui; Wang, Tianqi; Tajuddin, Dewi (Universiti Teknologi MARA Cawangan Sarawak, 2024)
In the context where sustainable development and corporate social responsibility have become universally accepted principles in the international community with moral requirements in market dynamics, corporate social responsibility (CSR) is not only a hidden moral pursuit and realistic transformation, but also the optimal strategic choice to expand market share and gain competitive advantages. However, there are still some enterprises which blindly prioritize corporate interests over social responsibility, resulting in a significant decline in corporate reputation, and even incurring major costs like risk of bankruptcy. Thus, to examine the impact of corporate social responsibility on strategic risk and the moderating effect of ethical decision-making have practical significance for promoting the practice of CSR and realizing the sustainable growth for enterprises. This research was conducted in Mainland China, where the researchers collected 423 samples using questionnaires through the field investigation of 35 enterprises in Henan, Ningxia and Guangdong provinces. The findings indicate that corporate social responsibility, both internal and external stakeholder responsibilities, can considerably decrease the strategic risks faced by enterprises, including operational, asset, competitive, and reputation risks. Additionally, with the moderating effect of ethical decision-making, internal and external stakeholder responsibilities have distinct impacts on the various dimensions of strategic risk. These findings not only deepen the theoretical knowledge of CSR but also offer valuable insights for the strategic risk management of enterprises in China.